2019
DOI: 10.1108/ijebr-04-2018-0274
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical invention in entrepreneurship education

Abstract: Purpose Following the example of the critical management education tradition, the purpose of this paper is to argue whether we should keep EE vital by disturbing it, in particular by interrogating that which has seemingly become “untouchable” from interrogation. Design/methodology/approach This paper takes inspiration from Paolo Freire’s work by proposing a pedagogical approach to entrepreneurship education which builds on an iterative and interactive process, oscillating between deconstructing and reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 83 publications
0
8
0
3
Order By: Relevance
“…Entrepreneurship is not suitable for everyone. While teaching entrepreneurship, we should understand the significance of education and learning (Verduijn and Berglund, 2019) and carry out critical entrepreneurship education (Komulainen et al, 2020). In the process of entrepreneurship education, there may be some conflict between entrepreneurial culture and traditional academic values, especially in the area of technology transfer (Gorovitz and Bok, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurship is not suitable for everyone. While teaching entrepreneurship, we should understand the significance of education and learning (Verduijn and Berglund, 2019) and carry out critical entrepreneurship education (Komulainen et al, 2020). In the process of entrepreneurship education, there may be some conflict between entrepreneurial culture and traditional academic values, especially in the area of technology transfer (Gorovitz and Bok, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…The study revealed that the participation of the students subjected to the teaching method was relatively high, and several suggestions were also provided for improving the teaching method. Verduijn and Berglund (2020) proposed the introduction of critical pedagogy into the classroom teaching of entrepreneurship education. Here, in the process of deconstructing and reconfiguring the start-up, teachers treat students as co-learners, arouse their curiosity, and encourage co-creation.…”
Section: Theoretical Significance and Practical Enlightenmentmentioning
confidence: 99%
“…The aforementioned studies are based on the belief that there is a need for re-evaluation of the effectiveness of traditional classroom teaching methods (CTMs) in cultivating students' entrepreneurial ability and spirit, especially in certain developing countries, where it is not necessarily possible for every student to directly set up a company to implement the teaching method of "learning by doing." Existing comparative studies on different teaching methods of entrepreneurship education have mostly adopted qualitative research (Nabi et al, 2017;Balan et al, 2018;Lackéus, 2020;Verduijn and Berglund, 2020), while quantitative research support remains relatively minimal. For the research object, only a certain type of major (Souitaris et al, 2007;Liñán and Chen, 2009;Mukesh et al, 2020;Rosado-Cubero et al, 2021) or a certain type of University (Ismail et al, 2018) was selected in many of the existing studies.…”
Section: Introductionmentioning
confidence: 99%
“…The final article in this special issue by Verduijn and Berglund (insert page numbers) provocatively opens up the “black box” of EEE, itself, through the application of insights from critical entrepreneurship studies (Berglund and Verduijn, 2018) to offer ways to both deconstruct and reconstruct entrepreneurship education.Deconstructing as we see it is concerned with interrogating dominant constructions of entrepreneurship (Nodoushani and Nodoushani, 1999; Ogbor, 2000)… Taken together these approaches do not suggest to criticize and “stop” entrepreneurship, but to enact it with more concerns for context – indeed, more concerns for global politics, and civil society – by resisting to adopt a too narrow interpretation, a one-size-fits-all approach, and avoiding to position entrepreneurship as “the solution”, denying its dark and grey sides (Hytti, 2018). This not only provides suggestions with regards to how to teach entrepreneurship in the classroom, but also for how we can rethink entrepreneurship curricula, programmes and the idea of the entrepreneurial university (Hytti, 2018; Tunstall, 2018) (Verduijn and Berglund, in this issue, #-#)…”
Section: Articles In the Special Issuementioning
confidence: 99%